Pengaruh Pelatihan, Kompensasi Finansial dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan pada RSUD Dr. Soediran Mangun Sumarso Wonogiri - Salsabilla Tasya Reviana Putri; Lukman Hakim (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the impact of training, financial compensation, and work environment on employee productivity at RSUD dr. Soediran Mangun Sumarso Wonogiri. The sample consists of 94 respondents selected using purposive sampling with the criterion of employees who have worked for at least one year. Data were collected through questionnaires with a Likert scale, and analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS software. The results show that training, financial compensation, and work environment have a positive and significant effect on employee productivity. Training improves skills and professionalism, financial compensation affects employee well-being and job satisfaction, and a supportive work environment is crucial for task effectiveness. This study has limitations in terms of the variables studied and the use of online questionnaires, which may affect data accuracy. Future research is recommended to include additional variables and use interview or direct observation methods to obtain more accurate data.